Social-Emotional and Behavioral Support for First- and Second-Grade Black Learners at Risk for Emotional and Behavioral Problems. (July 2023) - Campbell, Aaron Rachelle; Sallese, Mary Rose; Thompson, Julie L.; Burke, Mack D.; Allen, Meghan L.
There is a need to provide evidence-based social, emotional, and behavioral interventions for learners at risk for emotional and behavioral problems. Evidence-based interventions for social and emotional success are especially necessary for Black learners with emotional or behavioral problems. In the current study, we used a multiple-baseline design time-lagged across groups (i.e., classrooms) to examine the effects of a culturally adapted version of the Strong Start curriculum plus Check-In/Check-Out on externalizing problem behaviors of 18 first-grade and second-grade Black learners. Results indicate a functional relation between the intervention package and externalizing problem behaviors. Additionally, post-intervention social validity assessment indicates that participating teachers viewed the intervention package as feasible and participating learners reported a positive experience.